2010
DOI: 10.1007/s10800-010-0109-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical process for the treatment of landfill leachate

Abstract: In this paper, the anodic oxidation of a real leachate from an old municipal solid waste landfill has been studied using an electrolytic flow cell equipped with a lead dioxide (PbO 2 ) anode and stainless steel as the cathode. The influence of several operation parameters such as (i) the applied current (from 0.5 to 3 A), (ii) liquid flow rate (from 50 to 420 L h -1 ), (iii) temperature (from 25 to 50°C), and (iv) pH (from 3.5 to 8.2) on the COD removal rate, current efficiency, and energy consumption has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 52 publications
0
31
1
Order By: Relevance
“…Compared to the current study results, somewhat lower removal efficiencies of COD (60% to 92%) were obtained by other researchers using electrooxidation methods (8)(9)(10)(11)(12)(13). By applying electrooxidation process, 92% of the COD and 100% of ammonium was removed from the old landfill leachate using titanium anode coated with Sn-PdRu oxides (8).…”
Section: Resultscontrasting
confidence: 84%
“…Compared to the current study results, somewhat lower removal efficiencies of COD (60% to 92%) were obtained by other researchers using electrooxidation methods (8)(9)(10)(11)(12)(13). By applying electrooxidation process, 92% of the COD and 100% of ammonium was removed from the old landfill leachate using titanium anode coated with Sn-PdRu oxides (8).…”
Section: Resultscontrasting
confidence: 84%
“…= 104, pH = 6.5, reaction temperature = 30 ± 1°C, reaction time = 300 min, number of stepwise addition = 7. Panizza et al (2010) utilized anodic oxidation using electrolyte flow cell equipped with lead dioxide (PbO 2 ) anode and stainless steel as cathode. They observed that the galvanostatic electrolyses enhanced COD removal along with rising current, solution pH and temperature.…”
Section: Advanced Biological/physical-chemical Techniquesmentioning
confidence: 99%
“…[3,6] Leachates are mainly generated by (i) the natural precipitation and runoff in landfill site, (ii) the original water in the wastes, and (iii) decomposition processes occurring in the wastes. [7] The natural precipitation and runoff in landfill site are the main sources of leachate. It is a specific type of wastewater with a complex composition, containing large amounts of organic pollutants, ammonia nitrogen, inorganic salts, and heavy metals, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[2,9] The old landfill leachate (i.e., >10 years old) contains biorefractory compounds such as humic and fulvic acids, and is characterized by a low chemical oxygen demand (COD < 4000 mg L −1 ) and biological oxygen demand/ chemical oxygen demand ratio (BOD/COD < 0.1), so it is a kind of refractory and high concentrated organic wastewater. [7,10] At present, the treatments of landfill leachate are mainly physical-chemical method and biological method. [3] Because of their high cost-effectiveness and simplicity, biological treatments such as activated sludge, aerated lagoons, sequencing batch reactors, and upflow anaerobic sludge blanket reactors are widely and effectively used to treat the young leachate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation